Mice lacking microRNA 133a develop dynamin 2–dependent centronuclear myopathy - Liu, Ning (American Society for Clinical Investigation, 2011)
MicroRNAs modulate cellular phenotypes by inhibiting expression of mRNA targets. In this study, we have shown that the muscle-specific microRNAs miR-133a-1 and miR-133a-2 are essential for multiple facets of skeletal muscle function and homeostasis in mice. Mice with genetic deletions of miR-133a-1 and miR-133a-2 developed adult-onset centronuclear myopathy in type II (fast-twitch) myofibers, accompanied by impaired mitochondrial function, fast-to-slow myofiber conversion, and disarray of muscle triads (sites of excitation-contraction coupling). These abnormalities mimicked human centronuclear myopathies and could be ascribed, at least in part, to dysregulation of the miR-133a target mRNA that encodes dynamin 2, a GTPase implicated in human centronuclear myopathy. Our findings reveal an essential role for miR-133a in the maintenance of adult skeletal muscle structure, function, bioenergetics, and myofiber identity; they also identify a potential modulator of centronuclear myopathies.